REMOTE TEACHING: DILEMMAS AND REFLECTIONS FROM THE SUPERVISED INTERNSHIP DISCIPLINE - Zanlorenzi, Maria Joselia [UNESP]; Sandini, Sabrina Pla (Fundacao Univ Tocantins, 2022)
This text shares some reflections on the didactics in the formation of teachers in the Pedagogy course from the experience as supervisor teachers in the discipline of Supervised Internship, using remote teaching to develop the practical activities of the discipline. This is a theoretical study of a qualitative nature in which we present and problematize our challenges and dilemmas experienced during the suspension of on-site classes, but which did not exempt us from developing the practical moments of the discipline in Basic Education schools. The alternatives created for the moments of intervention in the school to happen, raised some questions about the didactics in the formation of teachers and the importance of teaching to act professionally in the face of the unexpected and unknown. Thus, in the light of Paulo Freire's writings, we talk about the situations experienced, weaving reflections on didactics and its importance in teacher education.
Keywords: Pedagogy; Initial Teacher Training; Didactic